2009
DOI: 10.1242/jeb.026856
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of H+-ATPase and carbonic anhydrase in intestinal HCO3– secretion in seawater-acclimated rainbow trout

Abstract: SUMMARYPyloric caeca and anterior intestine epithelia from seawater-acclimated rainbow trout exhibit different electrophysiological parameters with lower transepithelial potential and higher epithelial conductance in the pyloric caeca than the anterior intestine. Both pyloric caeca and the anterior intestine secrete HCO 3 -at high rates in the absence of serosal HCO 3 -/CO 2 , demonstrating that endogenous CO 2 is the principal source of HCO 3 -under resting control conditions. Apical, bafilomycin-sensitive, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 45 publications
4
64
1
Order By: Relevance
“…It has been noted that the preparation of DIDS is key to its efficacy (Grosell et al, 2009b), and such precautions were taken in the present study. We thus conclude that the HCO 3 -excretion mechanism is relatively DIDS insensitive in loach and similar to that seen in trout and flounder (Grosell et al, 1999;Grosell et al, 2009a).…”
Section: Gut Membrane Fluiditysupporting
confidence: 87%
See 4 more Smart Citations
“…It has been noted that the preparation of DIDS is key to its efficacy (Grosell et al, 2009b), and such precautions were taken in the present study. We thus conclude that the HCO 3 -excretion mechanism is relatively DIDS insensitive in loach and similar to that seen in trout and flounder (Grosell et al, 1999;Grosell et al, 2009a).…”
Section: Gut Membrane Fluiditysupporting
confidence: 87%
“…All the inhibitor stocks used in this study were also recently used in similar in vitro studies on toadfish and trout, which confirmed their efficacy (Grosell and Genz, 2006;Grosell et al, 2009a;Genz et al, 2011).…”
Section: Electrophysiology and Ph-stat Analysissupporting
confidence: 69%
See 3 more Smart Citations